ANALISA PENGARUH JUMLAH LILITAN DAN DIAMETER TEMBAGA PADA TRAFO TERHADAP DAYA OUTPUT MESIN SPOT WELDER AND SOLDERING IRON SEMI PORTABLE - Sedjati, Moch. Ari Wibowo; Wulandari, Diah (Universitas Negeri Surabaya, 2022)
In the welding process, there are still some obstacles, namely the welding equipment used still requires a large amount of electricity. For this reason, a welding tool that has relatively small electrical power is needed, it requires a transformer that is able to cut electrical power. To answer the above problems, the author is interested in developing a MOT (Microwave Oven Transformer) transformer whose secondary winding is modified as an alternative to conventional transformers so that the electric power becomes small. This plan aims to make a transformer with an output power of 450 Watt on a